2020
DOI: 10.1021/acsaem.0c01010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fuel Decomposition in the Presence of Colloidal Functionalized Graphene Sheet-Supported Platinum Nanoparticles

Abstract: Experiments and simulations were used to demonstrate that decorating functionalized graphene sheets (FGSs) with platinum nanoparticles (Pt@FGS) stabilized these particles. Addition of these particles to liquid hydrocarbon fuels was observed to significantly affect decomposition under supercritical conditions at a pressure of 4.75 MPa and temperatures from 753 to 803 K. The suspension of only 50 ppmw Pt@FGS in the fuel (equivalent to adding 10 ppmw Pt) enhanced fuel conversion rates (by up to 24%) with a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
10
1
Order By: Relevance
“…The fraction of hydrogen molecules is evaluated as the fraction of hydrogen atoms in hydrogen molecules among all hydrogen atoms in the simulation. We find that as T increases, more H 2 gas is generated, as expected because the Pt NP attracts and removes hydrogen from the hydrocarbons during the catalytic dehydrogenation process, and the adsorbed hydrogen atoms “roam” on the Pt surface, forming hydrogen molecules, and subsequently desorb from the Pt surface . Furthermore, we find that simulations with graphene oxide yield more H 2 than those without graphene oxide.…”
Section: Resultscontrasting
confidence: 49%
See 3 more Smart Citations
“…The fraction of hydrogen molecules is evaluated as the fraction of hydrogen atoms in hydrogen molecules among all hydrogen atoms in the simulation. We find that as T increases, more H 2 gas is generated, as expected because the Pt NP attracts and removes hydrogen from the hydrocarbons during the catalytic dehydrogenation process, and the adsorbed hydrogen atoms “roam” on the Pt surface, forming hydrogen molecules, and subsequently desorb from the Pt surface . Furthermore, we find that simulations with graphene oxide yield more H 2 than those without graphene oxide.…”
Section: Resultscontrasting
confidence: 49%
“…Polyethylene with a Pt NP, but without graphene oxide (green curve), shows a similar conversion rate compared to the case of PE with the Pt NP alone. This result is in contrast to the catalytic fuel decomposition using graphene-supported Pt NPs, where graphene oxide enhances the reaction rate. The difference might be due to the higher molecular mass and density of hydrocarbons used in our simulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation results revealed that the JP-10 decompositions initiated by either H or OH on the FGS reacted at a relatively lower energy barrier, compared to the unimolecular decompositions or reactions with O 2 , which then greatly promoted JP-10 initiation. More recent ReaxFF-MD studies of Hyung et al supported the catalytic mechanisms in which synergy between Pt-cluster and FGS was found to catalyze n -C 12 H 26 and MCH (methylcyclohexane) decomposition. , The simulation results indicated that the synergy of Pt-cluster and FGS effectually enhanced the initial dehydrogenation, which further formed the n -C 12 H 25 /C 7 H 13 radical.…”
Section: Introductionmentioning
confidence: 86%